Selected Euro-Area Countries : Rules-Based Fiscal Policy and Job-Rich Growth in France, Germany, Italy and Spain. (IMF Staff Country Reports; Country Report ;, 2001)
Fiscal deficits and the public debt has grown throughout much of the postwar period in most industrialized countries under the pressure of rising public expenditure, a trend that has begun to reverse after 1992. A number of studies argue that fiscal consolidation in association with expenditure restraint, particularly reductions in primary current expenditure, has proved more durable historically. All in all, the fiscal consolidation essential to qualify for European Monetary Union is a major achievement but also a difficult process in the four countries (France, Germany, Italy, and Spain).